2016
DOI: 10.1007/s40273-016-0462-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic Considerations in Treating Actinic Keratosis: An Update

Abstract: Actinic keratosis is one of the most common dermatological diagnoses worldwide, especially among the elderly, fair-skinned, and immunocompromised, and is associated with a risk of transformation to skin cancer. With actinic keratosis and skin cancer prevalence increasing as the aged population expands in the US, optimizing treatment strategies may produce cost savings for the healthcare system. Since the time of our last review in 2008, investigation of the economic considerations in treating actinic keratosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Pharmacoeconomics studies have described 5‐FU as an inexpensive, cost‐effective AK treatment, with great success rates . Immunosuppressed and organ transplanted patients have AKs that are refractory to treatment and progress more rapidly to invasive squamous cell carcinoma .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacoeconomics studies have described 5‐FU as an inexpensive, cost‐effective AK treatment, with great success rates . Immunosuppressed and organ transplanted patients have AKs that are refractory to treatment and progress more rapidly to invasive squamous cell carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…59 Pharmacoeconomics studies have described 5-FU as an inexpensive, cost-effective AK treatment, with great success rates. [60][61][62] Immunosuppressed and organ transplanted patients have AKs that are refractory to treatment and progress more rapidly to invasive squamous cell carcinoma. 63 Although this study did not consider immunosuppressed individuals, patients included had intense actinic damage, 86% fair skin, 82% personal history of multiple AK and 70% personal history of non-melanomas cutaneous tumours, which could justify the 32.5% prevalence of lesions treated incompletely by 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…The most common precursor of iSCC is actinic keratosis (AK), a highly prevalent lesion in adulthood: approximately 30% of the dermatology outpatient population in Spain aged ≥45 years old have AKs . As life expectancy increases, the incidence of AK is continuing to rise . AK may remain stable for long periods of time, undergo temporary or permanent regression, or evolve into iSCC .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the efficacy of the topically applied gel in the field therapy of AKs and its effect on the clearance of both clinically evident and subclinical lesions [10,12,31,35]. In a long-term follow-up study, Garbe et al [36] reported a persisting clinical clearance in 50% of the patients after 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally hypothesized that type III AKs had the main risk of progression, but in 2015, Fernandez‐Figueras et al showed that AKs type 1 actually are the most common lesions associated with invasive SCC; AKs type 2 and AKs type 3 can also progress to SCC albeit with a lower frequency. For this reason, treatment of all AK‐types is generally recommended, and numerous reviews have described the benefits of early therapeutical interventions .…”
Section: Introductionmentioning
confidence: 99%